Problematika Pembelajaran Terpadu di Madrasah Ibtidaiyah - Basiran; Sholeh, Mohamad (J-PGMI: Jurnal Pendidikan Guru MI, 2024)
This research investigates the implementation of integrated learning at MI Miftahul Falah Karanganyar, a primary school located in a rural area. Employing a qualitative approach, the study aims to comprehend various aspects related to this approach, examining challenges of implementation, the role of teachers, its impact on students, innovative efforts, and positive social outcomes. The findings reveal uncertainty in understanding and implementing integrated learning, but also emphasize the pivotal role of teachers who have effectively applied it. Students at the school have experienced holistic understanding, and innovative efforts and collaboration with the local community have the potential to enhance the quality of education. These findings support the theoretical perspectives of experts on relevance, inclusivity, holistic education, and multiple intelligences. Recommendations include deeper teacher training and support for resources and facilities. This research provides guidance for schools and other stakeholders in creating more effective and relevant education in rural areas.